DOI: 10.11606/d.85.2003.tde-07052007-161852
|View full text |Cite
|
Sign up to set email alerts
|

"Aplicação da difração e flourescência de raios-X (WDXRF): ensaios de argilominerais"

Abstract: Clay minerals are structural elements of soil applied in agreement with its properties. The characterization of this material has been necessary for technological, environmental, ecological and legal factors. In this scope to make possible a fast methodology, safe and efficient is especially important. In this work two procedures are described, the first to identify the clay minerals found in loamy soils by x-ray diffraction and the second determine quantitative constituent macro and micro of the clay by x-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
17

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 16 publications
1
5
0
17
Order By: Relevance
“…The XRD patterns of heated samples did not show the characteristic peaks of kaolinite (dioctahedral). This result verified the presence of kaolinite in both clays [44]. The results obtained in this work for both clay samples showed that the dominant clay minerals were illite and kaolinite.…”
Section: [Tabela I -Resultados Da Análise Granulométrica Das Amostrassupporting
confidence: 85%
See 1 more Smart Citation
“…The XRD patterns of heated samples did not show the characteristic peaks of kaolinite (dioctahedral). This result verified the presence of kaolinite in both clays [44]. The results obtained in this work for both clay samples showed that the dominant clay minerals were illite and kaolinite.…”
Section: [Tabela I -Resultados Da Análise Granulométrica Das Amostrassupporting
confidence: 85%
“…4b), illite was identified by the presence of peaks (001) at 10.29 Å and (002) at 4.98 Å while kaolinite was detected by the peaks (001) at 7.16 Å and (002) at 3.58 Å. The illite peak (003) at 3.3 Å was overlapped by the quartz peak at 3.35 Å. Quartz peak (001) was not present [44]. The XRD patterns of glycolated samples showed small variations in the position of the illite peak (001) of Taubaté clay, whereas that peak of Tremembé clay remained at 10.29 Å.…”
Section: [Tabela I -Resultados Da Análise Granulométrica Das Amostrasmentioning
confidence: 97%
“…This procedure is performed to assist the clay minerals identification. The ethylene glycol treatment is used to identify expansible minerals, allowing distinguish the smectite group minerals, while the heat treatment promotes the disappearance of the kaolinite, smectite and gibbsite peaks due to loss of the mineral crystalline structure that becomes amorphous to X-rays (SCAPIN, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Assim, interpolando-se nessa curva a cps do elemento de uma amostra desconhecida, determina-se a sua concentração (Pimentel et al, 1996;Souza 2007 espessura infinita e tem uma superfície razoavelmente plana (Lachance et al, 1995;Scapin, 2003). Na etapa da previsão é necessário estimar primeiramente uma composição aproximada da amostra.…”
Section: Páginaunclassified
“…O método de parâmetros fundamentais (FP) utiliza algoritmos que permitem calcular a composição química de uma amostra, sem a utilização de padrões similares, a partir da medida da intensidade da linha de emissão do analito e dos valores tabelados dos principais parâmetros fundamentais, como distribuição espectral primária (fonte), coeficiente de absorção (fotoelétrico e de massa), rendimento de fluorescência e outros (Bertin, 1970;Lachance et al, 1995;Nagata et al, 2001;Scapin, 2003;Scapin, 2008).…”
Section: Método De Parâmetros Fundamentaisunclassified